From the history of the formation of the international human rights system (Part II) (International relations and international law Journal, 2018)
The relevance of human rights and inalienable from it Freedoms is specific, peculiar, and perhaps the most fundamental institution in the framework of modern international human rights law and in the study obliges certainly take into account its own characteristics, developed and developing in-law as well as fundamental general theoretical ideas. The article is devoted to the history of evolution of the protection of human rights since the end of the VI-V century BC, where in ancient city that existed in ancient Rome and Athens originated the idea of human rights and freedoms, namely the so-called «civil concept» and to the middle of the XIX century. In the article a lot of attention is paid to the content of formation and functioning of the international human rights system.Key words: individual, international system, human rights, equality, freedom.